2011
DOI: 10.4097/kjae.2011.60.6.416
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative nausea and vomiting after endoscopic thyroidectomy: total intravenous vs. balanced anesthesia

Abstract: BackgroundEndoscopic thyroidectomy was recently introduced and has been rapidly accepted by surgeons and patients. The present study was conducted to estimate and compare the incidences of postoperative nausea and vomiting (PONV) after endoscopic thyroidectomy using two different anesthetic methods: sevoflurane based balanced anesthesia; total intravenous anesthesia (TIVA).MethodsNinety nine female patients that were scheduled to undergo elective endoscopic thyroidectomy under general anesthesia were enrolled.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 19 publications
4
18
2
Order By: Relevance
“…This finding confirms studies that indicate there is no difference in the total recovery time of patients anesthetized with TIVA using propofol and patients anesthetized with inhalational anesthesia using sevoflurane [6,12].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This finding confirms studies that indicate there is no difference in the total recovery time of patients anesthetized with TIVA using propofol and patients anesthetized with inhalational anesthesia using sevoflurane [6,12].…”
Section: Discussionsupporting
confidence: 80%
“…These results contradict studies that found the incidence of PONV to be significantly reduced in patients that received TIVA with propofol compared to patients that received inhalational anesthesia using sevoflurane [6,9,10] or inhalational anesthesia using other volatile anesthetics [11,12]. Although our study was limited by the number of patients enrolled (n=23), our findings are consistent with other larger studies that compared the incidence of PONV in patients anesthetized with TIVA using propofol and patients anesthetized with inhalational anesthesia using sevoflurane.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Eight studies investigated postoperative nausea and vomiting, with 371 patients receiving propofol and 354 patients receiving inhalational anaesthesia [10,19,20,22,24,25,28,30]. Propofol was associated with a significant reduction in postoperative nausea and vomiting (relative risk (95% CI) 0.446 (0.304-0.656) (p < 0.0001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the prevention and treatment of nausea and vomiting have become important subjects in anesthesiology [3]. Currently, even with new anesthetic techniques, which involve the use of prophylactic agents and the selection of anesthetics with lower emetic potentials, the incidence of PONV has not decreased and is still approximately 20% to 30% [4] [5] [6].…”
Section: Introductionmentioning
confidence: 99%